Decolorization of anthraquinone, azo and triphenylmethane dyes by laccase from newly isolated fungus, Cerrena sp. BMD.TA.1. (August 2019) - Hidayat, A; Ningrum, A C; Falah, S
Abstract: The use of white-rot fungus for dyestuff degradation is alternative of eco-friendly strategy on removal of industrial effluents. This study was conducted to investigate the decolorization of dyes using laccase produced by Cerrena sp. BMD.TA.1 isolated from Gunung Rinjani National Park (GRNP), West Nusa Tenggara – Indonesia. This fungus had capability to decolorize three types of dyes, those: anthraquinone (Remazol Brilliant Blue R, RBBR), azo (Congo Red) and triphenylmethane (Fast Green FCF). The optimum laccase activity in this dyes treatment by fungal culture was achieved at 96 h pre-incubation, but the highest decolorization rate was reached at 144 h pre-incubation. After 72 h of dyes treatment, all dyes were removed at least 82%. The optimum decolorization for 100 mg L −1 was similar for of all dyes types. The decolorization of RRBR was higher compared to Congo Red and Fast Green FCF at 1000 mg L −1 . Furthermore in purified laccase, the RBBR was decolorized without any addition of redox mediator. The decreasing of laccase activities and increasing of dye concentration resulted on the lowest decolorization.This study revealed that laccase produced by Cerrena sp. BMD.TA.1 contributed to decolorization process, and had potential industrial application on removal of dyes effluents.